Fock-space multi-reference coupled-cluster response with the effect of triples on dipole moment of ClO and SF radicals - Ravichandran, Lalitha; Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (Journal of Chemical Sciences, 2012)

Electronic transition dipole moments and dipole oscillator strengths within fock-space multi-reference coupled cluster framework: an efficient and novel approach - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2013)
Within the Fock-space multi-reference coupled cluster framework, we have evaluated the electronic transition dipole moments, which determine absorption intensities. These depend on matrix elements between two different wave functions (e. g., ground state to the excited state). We present two different ways, to calculate these transition moments. In the first method, we construct the ground and excited state wave functions with the normal exponential ansatz of Fock-space coupled cluster method and then calculate the relevant off-diagonal matrix elements. In the second approach, we linearize the exponential form of the wave operator which will generate the left vector, by use of Lagrangian formulation. The right vector is obtained from the exponential ansatz. In order to relate the transition moments to oscillator strengths, excitation energies need to be evaluated. The excitation energies are obtained from the Fock-space multi-reference framework. The transition dipole moments of the ground to a few excited states, together with the oscillator strengths of a few molecules, are presented. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4793277]

Electronic transition dipole moment: a semi-biorthogonal approach within valence universal coupled cluster framework - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2014)
Electronic dipole strengths (square of transition moments) and oscillator strengths are evaluated for various transitions, arising from the ground state to a few valence excited states. Parallel to two other methods of calculating the dipole strength within the Fock-space multireference coupled cluster framework, a new semi-biorthogonal approach is formulated and implemented in this article. This semi-biorthogonal approach can evaluate dipole strengths at a lower computational effort than the biorthogonal approach without compromising on the accuracy. This new method is compared and tested against the previously developed expectation value and biorthogonal approach for various molecular transitions. (C) 2014 Wiley Periodicals, Inc.
Keywords: electronic transition dipole; Fock-space; oscillator strength; semi-biorthogonal expectation value

Perturbative order analysis of the similarity transformed hamiltonian in fock-space coupled cluster theory: difference energy and electric response properties - Bhattacharya, Debarati; Dutta, Achintya Kumar; Gupta, Jitendra; Pal, Sourav (Molecular Physics, 2015)
A perturbative analysis of the ground-state similarity transformed Hamiltonian and its effect on the various Fock-space coupled cluster (FSCC) sectors is presented through calculation of ionisation potential, electron affinity, excitation energies and response properties. Various truncation schemes of the effective Hamiltonian are presented with explicit form of the defining equations. Based on such a truncation, the approximate methods are labelled as FSCC(n), where n represents the correlation energy of the ionised, electron attached or excited states corrected at least up to nth order within coupled cluster singles and doubles scheme (CCSD). A lower scaling CC2 type of approach (abbreviated as FS-CC2) is compared against the group of FSCC(n) methods for energies. Electric response properties have been compared and contrasted for the two lower scaling methods: FSCC(2) and FS-CC2. The various truncated methods are tested for a number of small molecules. The results obtained from a range of truncated methods are compared against full FSCCSD calculations.
Keywords: electric response properties; Fock space; perturbative order; similarity transformed Hamiltonian